When Educators Come Together to Speak About Well-Being: An Invitation to Talk - Simmons, Marlon; McDermott, Mairi; Lock, Jennifer; Crowder, Rachael; Hickey, Evelyn; DeSilva, Noeleen; Leong, Rebecca; Wilson, Katrina (Canadian Journal of Education/Revue canadienne de l’éducation, 2019)
Contingent on multiple variants, educators’ well-being is becoming a concern regarding quality of life in and out of schools. Our qualitative case study aimed to understand how educators negotiate well-being through ever-increasing complexities in schooling environments and incommensurable lifeworld realities. Findings include material relevant to (1) the cultural politics of well-being; (2) relationality of/with well-being; (3) the need for self-care; and (4) ways of being and doing well-being in context. Conclusions discuss how to support educators in creating and fostering well-being for themselves individually, and within collective and institutional levels. Keywords: educator well-being, school environment, community engagement and leadership, well-being resources, educator support